The Triadic Concept of The Bahtera Collective Script in The Learning Program with Maestro in Semiotics Perspective - Aji Jakaria; Jaeni; Nissa Agrarini (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
The Learning with Maestro (BBM) Program, initiated by the Ministry of Culture of the Republic of Indonesia, seeks to enhance art appreciation and cultivate student character through engagement with six art maestros: Ki Purbo Asmoro (dalang), Nasirun (painting), Sundari Soekotjo (music), Iman Soleh (theater), Gus TF Sakai (literature), and Didik Nini Thowok (dance). The BBM Theater Arts Program took place at Celah Celah Langit (CCL) in Bandung, with participants from eight distinct regions: Kupang, Bali, Aceh, Jambi, West Java, Banten, Yogyakarta, and Makassar. The objective of the study is to analyze Charles Sanders Peirce's triadic idea as it pertains to the Bahtera text, emphasizing representamen, object, and interpretant. This research employs a descriptive qualitative methodology, utilizing data collection approaches such as observation, interviews, and document analysis. This study yielded five principal findings: the symbol of co-existence, plurality index, ecological icon, symbol of materiality, and symbol of transcendence. The study concludes that the Bahtera script functions as a communal semiosis capable of fostering social, ecological, and transcendent consciousness through symbolic dramatic signs. Interviews were systematically executed by devising research instruments comprising questions pertinent to the research subjects. The researchers interviewed a participant in the BBM program who was intimately engaged in the scriptwriting process. The interview is semi-structured, designed to obtain a comprehensive understanding of the script's development background and the creative dynamics between the participants and the theater maestro in interpreting the script's symbolism.